Break Even Analysis of Poultry Egg Production in Rural Area in Southeast Sulawesi - Niu, Eryanti; Saediman, Haji; Surni, Surni (Bina Nusantara University, 2016)
This research aimed to analyze break-even point and margin of safety of poultry egg production in the rural area in Southeast Sulawesi. The research used a case study approach by using questionnaire1, in-depth interviews, and observation to collect data and information from a small-scale poultry egg producing enterprise which was selected purposively with the consideration that the farm is located in rural area and had less than 1.000 laying hens. Data were analyzed using costs and returns, break-even point, and margin of safety ratio. Research results show that the enterprise record net income of Rp9.232.165,00. R/C ratio of 1,32 means that the enterprise would earn a revenue of Rp1,32 for every one rupiah it invested. Break even sales are Rp3.374.474,00 and break even volume was 140,60 kg. The egg production is far above both the break-even sales and units, meaning that the enterprise earns a profit from egg production. The margin of safety is Rp34.750.526,00 or 91,15%, indicating a high level of safety in the enterprise. In view of its profitability and the importance of poultry egg production in the generation of employment and fulfillment of protein needs of the population, local government and other stakeholders are suggested to take measures to promote poultry egg production in rural areas by providing technical assistance program for small-scale poultry farmers at the community level and improving managerial skills in the poultryegg production.